Evidence of disseminated infection by Mycobacterium avium subspecies hominissuis in a pet ferret (Mustela putorius furo). (December 2016) - Bezos, Javier; Álvarez-Carrión, Beatriz; Rodríguez-Bertos, Antonio; Fernández-Manzano, Álvaro; de Juan, Lucía; Huguet, Cristina; Briones, Víctor; Romero, Beatriz
Abstract: The infection caused by the zoonotic opportunistic pathogen Mycobacterium avium subsp. hominissuis (Mah) was reported for the first time in a pet ferret. Both owners were HIV-positive. Euthanasia of the pet was recommended due to medical reasons and as a preventive action. Disseminated and open tuberculosis lesions were observed in the gastrointestinal and respiratory systems of the ferret. Ecographic and radiographic surveys showed a severe generalized lymphadenopathy, strong thickening of the gastric wall and peritoneum layer. The histopathological findings revealed a disseminated, granulomatous, chronic inflammation affecting the gastrointestinal tract, lungs, lymphoid tissues (spleen, tonsils and lymph nodes) and liver. Ziehl-Neelsen staining displayed the presence of positive acid-fast bacilli within these granulomas. Bacteriology and sequencing of the isolates yielded Mah sequevar code 3. Ferrets can act as reservoirs of mycobacteria exposing their owners to the infection, which is of major concern in immunodeficient individuals, as those HIV-infected. Highlights: Mycobacterium avium subsp. hominissuis (Mah) infection was reported for the first time in a pet ferret. The histopathological findings revealed a disseminated infection. Potential excretion was demonstrated by the presence of mycobacteria in the respiratory and digestive tracts.